Stock Market Liquidity and The Macroeconomic Fluctuations: UK Empirical Study - Mao, Jianlei (2010)
This paper investigates the relationship between stock market liquidity and macro economy fluctuations in UK. The sample covers all the common shares (620 firms in total) listed in London Stock Exchange over the period 1989-2009. By comparing the large-firm portfolio and small-firm portfolio results, we conclude that the theoretical ‘flight to quality’ phenomenon is observable in UK stock market, however, the effect is relative weaker than the one observed in US market.